Character Strengths as Manifestations of Spiritual Life: Realizing the Non-Dual From the Dual - Littman-Ovadia, Hadassah; David, Amnon (Frontiers in Psychology, 2020)
There is a noticeable increase of interest in the study of spirituality within the context of positive psychology. The literature review shows several parallels between dimensions of spirituality as explored within psychology of religion and spirituality, and those of the VIA model of character strengths (CS) as developed in positive psychology. However, coming from the domain of psychology rather than theology, these studies do not go deep into the paradoxes that exist at the heart of various traditions regarding the nature of the spiritual or non-dual. Moreover, these studies lack a more comprehensive view of the nature of CS and virtues. Our suggestion is to expand CS science to a wider context, extend perspective from the individual to the transcendent and understand actualization of CS’ capacities as pathways to spiritual life. We argue that actualization of all CS allows for microcosms of a realization of unity. We believe that framing VIA’s CS as a classification of the positive human spirit, and therefore rightfully placing it in the domain of human spirituality, holds great potential for both domains. We start by considering common basic assumptions emerging from various spiritual traditions, and continue with a suggestion to see CS as various pathways from duality to non-duality, illustrating ways in which spirituality can be understood and practiced by the use of CS.